Religious Extremism and the Challenges of De-radicalisation in Nigeria's North East Region - Ngboawaji Daniel Nte; Baba Ahmadu Abdulaziz; Awwal Isah; ClairmontFeatherstone (The Indonesian Journal of International Clinical Legal Education, 2021)
Nigeria is currently confronted with a number of security challenges, originating from forces of religious extremism. Boko Haram is an epitome of such security challenge that has continuously destabilized the Nation’s security. It is on this ground this research work was deemed necessary to try and de-mystify the challenges of de-radicalization. The research work studied religious extremism, with focus on its causes, upon which the challenges of de-radicalizing extremists were identified. In line with the research findings, the researchers drafted measures in form of recommendations that are deemed most suitable. Ultimately, having exploited both primary and secondary sources, the researchers adopted a mixed-methodology for data analysis and came to the conclusion that Islam or Christianity in their entirety do not sanction any form of violence. As such, other factors such as socialization, economy, politics etc were explored as causative factors and these formed a base for data collection and analysis, as well as the veritable recommendations proffered to stem the deadly scourge of violent extremism and terror ravaging Nigeria and the West African sub-region.